后纵隔细针穿刺细胞病理诊断髓外造血并文献复习 (Nan Fang Yi Ke Da Xue Xue Bao, 2017)
To study the feasibility of in a A patient with extramedullary hematopoiesis presenting as a posterior mediastinal tumor underwent fine-needle aspiration for cell pathology diagnosis. The primary locus of a posterior mediastinal extramedullary hematopoiesis was examined with Papanicolaou staining and HE staining, and the expressions of cytokeratin, epithelial membrane antigen (EMA), terminal deoxynucleotidyl transferase, CD3, CD20, anaplastic lymphoma kinase, CD34, CD235a, myeloperoxidase, CD61, P53, CD30, S-100, CD1a, and Ki-67 with immunohistochemistry. The results were analyzed of bone marrow biopsy and cell smears, examination of chromosome structure and number, and detection of BCR/ABL fusion gene using fluorescence in situ hybridization. Examination of cell pathology of fine-needle aspiration in the posterior mediastinal focus revealed scatter cells of heterogeneous sizes consisting mainly of erythroid cells, and granulocytes and erythroid cells at different stages and lobulated large mature megakaryocytes were found. The eythroid cells in the core biopsy tissue were distributed in multiple cell islands. Immunohistochemistry showed positive results for erythroid cell CD235a, granulocyte MPO, megakaryocyte CD61, and Ki-67 (about 90%). Examination of the bone barrow biopsy tissue and cell smear also showed the changes of hyperplastic anemia without clone structure or abnormal number of the chromosomes, and no BCR/ABL fusion gene was detected by fluorescence in situ hybridization. Fine-needle aspiration cell pathology combined with the patient's clinical data allows the diagnosis of extramedullary hematopoiesis in the rare site of the posterior mediastinum.